GENERAL HOSPITAL DESIGN WITH A TROPICAL ARCHITECTURAL APPROACH - Ariansyah - - (Universitas Mercu Buana, 2023)
Abstrak – The hospital is one of the important facilities in a city that requires complete and efficient facilities. Each city area in Jakarta has a regional general hospital that has facilities that can meet the needs of each city area. Hospital physiology is one thing that is very important for a hospital. The physical field, including buildings and spatial performance, landscaping, and supporting infrastructure, is beginning to be approached with indicators of comfort, beauty, and success in the environment, all of which build the image of health services in their class. a beautiful, functional, efficient and clean building gives a positive impression to all hospital users. The design of public hospitals with a tropical architectural approach is expected in the design of hospital buildings that are functional, safe, comfortable, healthy and beautiful, and fulfill aesthetic principles, but are also required to design buildings that are safe and do not cause problems for the environment and humans. in the short or long term. Buildings must be energy efficient and produce the lowest possible carbon emissions in terms of building technology.